Pengendalian Hama Kumbang Tanduk (Oryctes Rhinoceros) Menggunakan Fruit Trap dengan Kandungan Buah Nanas di Desa Payarengas Kecamatan Hinai Kabupaten Langkat - Ingrid Ovie Yosephine; Saroha Manurung; Rani Febriani Br Trg; Isni Hokikah Auliah; Hardiansyah, Hardiansyah (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2023)
One of the pests that attacks oil palm plants is Oryctes rhinoceros Linn, known as a pest that borers oil palm shoots by sucking fluids and making holes in the midribs of leaves, stems and fruit. This horn beetle pest attacks oil palm plants planted in the field until they are 2.5 years old by destroying the growing point, resulting in damage to young leaves. So far, control has been carried out using chemical pesticides. The consequences of excessive use of pesticides can cause environmental problems. To avoid these consequences, natural horn beetle pest control is carried out using pineapple juice. This program is carried out to provide knowledge to the public about how to control horn beetle pests (Oryctes Rhinoceros) using fruit traps containing pineapple fruit. Socialization activities for controlling horn beetles (Oryctes Rhinoceros) using fruit traps containing pineapple fruit in Payarengas Village, Hinai District, Langkat Regency for 1 month from 14 August to 14 September 2023. Installing fruit traps containing pineapple fruit in the land shows potential as a pest control horn beetles naturally. With community service activities, oil palm farmers can provide education and innovation in controlling horn beetle pests using fruit traps made from pineapples.